Performance of different organic fertilizers in improving growth and yield of boro rice (SAARC Journal of Agriculture, 2019)
A field experiment was conducted at two locations i.e. at Soil Science Field of Bangladesh Agricultural University and at Farmer’s field of Fakirakanda village of Mymensingh Sadar to evaluate the effects of different organic fertilizers on the growth and yield of rice (BRRI dhan28). The experiments at each location containing seven treatments were laid out in a randomized complete block design with three replications. The treatments were T0: Control, T1: 75% RFD; T2: 100% RFD, T3: 75% RFD + Kazi Jaibo Shar (5 tha-1), T4: 75% RFD + Kazi Jaibo Shar (3 t ha-1), T5: 75% RFD + Poultry manure (3 t ha-1) and T6: 75% RFD + Cow dung (5 t ha-1). Application of poultry manure as well as Kazi Jaibo Shar showed positive effects on yield attributes, grain and straw yields of rice, nutrient (N, P, K and S) contents and uptake by grain, straw and in total. The performance of 75% RFD with poultry manure @ 3 t ha-1 was the best in producing yield components, grain and straw yields of rice. At both locations, the performance of same dose (3 t ha-1) of poultry manure and Kazi Jaibo Shar was almost similar in producing growth and yield contributing characters, grain and straw yields, - nutrient content and uptake by rice while each of these manures compensated up to 25% of recommended chemical fertilizers. Therefore, considering the soil health, poultry manure or Kazi Jaibo Shar @ 3 t ha-1 is recommended for growth and yield enhancement in rice.SAARC J. Agri., 16(2): 153-166 (2018)